Long Term Delta-9-tetrahydrocannabinol Administration Inhibits Proinflammatory Responses in Minor Salivary Glands of Chronically Simian Immunodeficieny Virus Infected Rhesus Macaques - Xavier Alvarez; Karol Sestak; Siddappa N. Byrareddy; Mahesh Mohan (Viruses, 2020)
HIV/SIV-associated oral mucosal disease/dysfunction (HAOMD) (gingivitis/periodontitis/salivary adenitis) represents a major comorbidity affecting HIV patients on anti-retroviral therapy. Using a systems biology approach, we investigated molecular changes (mRNA/microRNA) underlying HAOMD and its modulation by phytocannabinoids (delta-9-tetrahydrocannabinol (∆9-THC)) in uninfected (n = 5) and SIV-infected rhesus macaques untreated (VEH-untreated/SIV; n = 7) or treated with vehicle (VEH/SIV; n = 3) or ∆9-THC (THC/SIV; n = 3). Relative to controls, fewer mRNAs were upregulated in THC/SIV compared to VEH-untreated/SIV macaques. Gene enrichment analysis showed differential enrichment of biological functions involved in anti-viral defense, Type-I interferon, Toll-like receptor, RIG-1 and IL1R signaling in VEH-untreated/SIV macaques. We focused on the anti-ER-stress anterior gradient-2 (AGR2), epithelial barrier protecting and anti-dysbiotic WAP Four-Disulfide Core Domain-2 (WFDC2) and glucocorticoid-induced anti-inflammatory TSC22D3 (TSC22-domain family member-3) that were significantly downregulated in oropharyngeal mucosa (OPM) of VEH-untreated/SIV macaques. All three proteins localized to minor salivary gland acini and secretory ducts and showed enhanced and reduced expression in OPM of THC/SIV and VEH/SIV macaques, respectively. Additionally, inflammation associated miR-21, miR-142-3p and miR-29b showed significantly higher expression in OPM of VEH-untreated/SIV macaques. TSC22D3 was validated as a target of miR-29b. These preliminary translational findings suggest that phytocannabinoids may safely and effectively reduce oral inflammatory responses in HIV/SIV and other (autoimmune) diseases.